Molecular identification of two Actinomycetes (Streptomyces sp. and Norcardia sp.) with the evaluation of cytotoxicity and antioxidant properties of Streptomyces sp. Extract (Texas Journal of Agriculture and Biological Sciences, 2023)
The current study was carried out to isolate Actinomycetes bacteria from soil samples from AlDiwaniyah City, Iraq, and to evaluate the toxicity and antioxidant characteristics of the extract of the isolated species. For that aim, 500gm of soil sample was collected and subjected to series of bacterial cultivation that ended up with bacterial identification using morphological, biochemical, and 16S rRNAgene-polymerase chain reaction (PCR) tools. The final identification revealed the isolation of two Actinomycetes; Streptomyces sp. (named as QZS11) and Nocardia sp. (named as QZS9), and since many members of Streptomyces are beneficial bacteria, the toxicity and antioxidant characteristics of the extract of the isolated QZS11 were evaluated using the Vero cell viability assay and the diphenyl picryl hydrazine (DPPH) reduction assay, respectively. The results showed that the viability rates of the Vero cells were 100% at 0.125mg/ml and 90% at 0.25mg/ml. The findings regarding the DPPH assay revealed an important antioxidant level (20%) at 0.25mg/ml. The study reports the isolation of two Actinomycetes; Streptomyces sp. (QZS11) and Nocardia sp. (QZS9), with low toxicity and important antioxidant level at a very low concentration for the QZS11 isolate.